2012
DOI: 10.1136/emermed-2011-200750
|View full text |Cite
|
Sign up to set email alerts
|

Emergency care provision at the 2009 Special Olympics Great Britain

Abstract: Allocation of the healthcare team was appropriate, with the exception of one sport, where a doctor was moved from a nearby event to consult on 13 occasions. Attendances to the local ED and UCC were minimal. Therefore, the model of on-site medical care that was used, which led to minimal impact on NHS resources, will support the arrangements of medical requirements at future SOLGB games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This concurs with findings by Williamson et al, who found that providers could address 93% of consultations on-site at the Summer Olympics Great Britain in Leicester. 18 Most injuries and illnesses would be referred for further evaluation in an emergency department at the cost of time and money to both SOPA and the athletes. Physicians and ATCs have the skills and training to evaluate and treat many injuries and illnesses.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…This concurs with findings by Williamson et al, who found that providers could address 93% of consultations on-site at the Summer Olympics Great Britain in Leicester. 18 Most injuries and illnesses would be referred for further evaluation in an emergency department at the cost of time and money to both SOPA and the athletes. Physicians and ATCs have the skills and training to evaluate and treat many injuries and illnesses.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%